Circulating progenitor cells in stable coronary heart disease and acute coronary syndromes: relevant reparatory mechanism?. Issue 1 (29th March 2007) - Wojakowski, W; Kucia, M; Kaźmierski, M; Ratajczak, M Z; Tendera, M
Abstract : Bone marrow-derived cells which may be involved in cardiac repair/regeneration after ischaemic injury must undergo mobilisation into peripheral blood with subsequent homing and engraftment into the target organ. Mobilisation of the heterogeneous population of stem/progenitor cells in endothelial injury or myocardial ischaemia has been described recently. The number of circulating stem/progenitor cells reflects the endothelial damage, and turnover may be a surrogate marker reflecting the burden of cardiovascular risk factors and prognostic markers in stable coronary heart disease and acute coronary syndromes. Acute coronary syndromes are associated with increased levels of inflammatory and haematopoietic cytokines which, in turn, can mobilise progenitor cells from the bone marrow. Myocardial infarction increases the number of endothelial progenitor cells and other less well-defined subpopulations, such as CD34/c-kit + and CD34/CXCR4 + cells, which may take part in cardiac repair after ischaemic injury. Data on mobilisation of stem/progenitor cells in acute coronary syndromes are summarised here. Cell types, mechanisms of mobilisation, homing and engraftment are discussed and their relevance to clinical outcomes.